أثر طرق الري على كفاءة استخدام المياه وعلى الإنتاج الكمي والنوعي للشوندر السكري في منطقة الغاب - هيفا, سوسن عبد الله; الجداوي, سمير; فاتي, رولا محمد (Latakia University Journal -Biological Sciences Series, 2014)
انطلاقا"من أهمية المحافظة على الموارد المائية في سوريا عموما وفي منطقة الغاب خصوصا" ومن أجل معرفة أثر طرق الري على الإنتاج النوعي و الكمي لمحصول الشوندر السكري المزروع في سهل الغاب, تم تطبيق ثلاث طرق للري (التنقيط, الرذاذ ,السطحي بالخطوط) على محصول الشوندر السكري بهدف دراسة أفضل طرق الري على هذا المحصول و للحصول على أفضل غلة مع رفع كفاءة استخدام المياه. وبينت النتائج تفوق طريقة الري بالرذاذ معنويا على الري بالتنقيط و السطحي في كفاءة استخدام المياه من حيث إنتاجية الجذور(18.04)كغ/م3 وكمية السكر النظرية(2.74 ) كغ/م3 وكمية السكر الفعلية (2.11) كغ/م3. في حين لوحظ تفوق طريقة الري السطحي معنويا" على طريقة الري بالرذاذ والتنقيط من حيث الإنتاج الكمي, حيث بلغت الإنتاجية (84.81 ) طن/ه و كمية السكر النظرية (12.36 (طن/ه وكمية السكر الفعلية (9.89) طن/ه. أما من حيث الإنتاج النوعي بينت النتائج تفوق طريقة الري بالتنقيط معنويا" على طريقتي الري بالرذاذ والسطحي حيث بلغت نسبة السكر في الجذور (15.36 )% ونسبة السكر في العصير (17.42)% ونسبة المواد الصلبة الذائبة في العصير (23.66)%. في حين لوحظ تفوق طريقة الري السطحي معنويا"على طريقة الري بالرذاذ والتنقيط من حيث نقاوة العصير (80.03)%.وخلصت هذه الدراسة إلى أهمية استخدام طريقة الري بالرذاذ في منطقة الغاب . Based on the importance of maintaining the water resources in Syria in general and in AL-Ghab Region, especially" and to know the impact of irrigation on production qualitative and quantitative of sugar beet whose planted in AL-Ghab Region,so the experiment was application with three methods of irrigation (drip, sprinkler, surface by lines) on sugar beet in order to study the best way of irrigation on this crop and to get the best yield with raising the efficiency of water use .The Results show that sprinkler irrigation surpassed significantly on drip and surface irrigation in the efficiency of water use for roots yield (18.04) kg/m3 and the amount of sugar theory (2.74 ) kg/m3 and the amount of actual sugar (2.11) kg/m3.While it was noted that the surface irrigation surpassed significantly on drip and sprinkler irrigation in the quantitative production , the highest root yield (84.81 ) t/ha and the amount of sugar theory (12.36) t/ha and amount of actual sugar (9.89) t/ha. either for qualitative production The Results show that drip irrigation surpassed significantly on sprinkler and surface irrigation, where the percentage of sugar in roots (15.36) % and the percentage of sugar in the juice (17.42)% and the proportion of solid substances dissolved in the juice (23.66) %. While it was noted that the surface irrigation surpassed significantly on drip and sprinkler irrigation in pure juice (80.03) % . This study concluded the importance of the use of irrigation sprays to match in AL-Ghab Region.